Η πολεµική τέχνη των πρώιµων Σλάβων (ΣΤ΄-Ζ΄ αι.) - ΚΑΡΔΑΡΑΣ Γεώργιος (Byzantina Symmeikta, 2009)
THE ART OF WAR OF THE EARLY SLAVS (6TH-7THC. A. D.) This study deals with the development of warfare among the early Slavs during the 6th and 7th c. A. D. Its main focus is based on the equipment, the tactic, the art of ship building, the use of the horse, the art of siege and the fortifications. The testimony of sources is critically viewed with respect to the above questions, while with regard to the equipment a number of archaeological data is also added. The conclusions reached, attribute to a large degree the development of the early Slav warfare to contacts with nomadic tribes, and the Avars in particular, with whom they conducted common attacks in Byzantine territory. In certain cases, the extensive use of the horse by the Slavs is attested, as against the traditional view that they usually fought as foot soldiers, and the absence of fortifications among the Slavs of the Lower Danube. The use of the Slavic light spear by the Byzantine army is also noticed.